(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The requirement for radio spectrum has been increasing and this has resulted in the materialization of wireless applications with enhanced features and higher data rate. The spectrum is scant, and the current radio spectrum regulation is making its use inefficient. This necessitates the development of new dynamic spectrum allocation policies to better exploit the existing spectrum. According to the present spectrum allocation regulations, specific frequency bands are allocated to particular services and only approved users are granted access to licensed bands. Cognitive radio (CR) is expected to modernize the mode spectrum is allocated. In a CR network, the intelligent radio part allows secondary users (unlicensed users) to access spectrum bands allocated to the licensed primary users with the avoidance of interference. A solution to this inefficiency has been highly successful in the ISM (2.4 GHz), the U-NII (5–6 GHz), and microwave (57–64 GHz) bands, by making the unused spectra accessible on an unlicensed basis. However, in order to obtain spectra for unlicensed operation, new sharing concepts have been introduced to allow the usage of spectra by secondary users under the prerequisite that they limit their interference to the primary users. This would start by studying techniques employed in the design of UWB filters. This study is aimed to investigate the filters for overlay and underlay CR. This paper presents a comparative study of ultra-wideband filters for Cognitive Radio Networks.